Design, Fabrication And Evaluation Of Composite Sandwich Panels For Crashworthiness - Tarlochan, Faris (2007)
As time progressed, so did the technology of transportation and today we have a range of motorized vehicles that run on fossil fuel. The number of these vehicles is increasing year by year throughout the globe. There are two negative issues on this. First, the demand on fuel will increase and the second is that due to the increase of vehicles on road, the number of accidents and casualties has also increased the last two decades to an alarming figure. These accidents are a serious issue for the country in terms of economic losses. In 2003 alone, Malaysia had a total economic lost of RM 9.3 billion due to road accidents. One of the potential solutions to is to reduce the overall fuel consumption by reducing the overall mass of the vehicle. Reducing vehicle mass by material substitution may have implications for vehicle safety. Substitution of a lighter material of equal strength and energy absorbing capacity in the body structure can maintain the same level of kinetic energy absorption and passenger protection, while reducing overall vehicle mass. Hence the present work is dedicated to the design and evaluation of a new crashworthy composite sandwich structure design. The research methodology adopted in this thesis work comprises of two stages. The initial stage was an investigation to the axial crushing response of normal or conventional composite sandwich panels. The second stage was the designing stage of a potential candidate energy absorber based on inputs received from the initial stage of the thesis. All specimens were fabricated by using hand wet lay up. It was found in the first stage that all of these conventional panels failed in a global column buckling manner. None showed any signs of progressive failure as expected in a crush energy absorber devise. While maintaining the same amount of constituent materials used, several “new” sandwich panels were designed and tested quasi – statically in the second stage. From these designs, one particular design termed as “wrap” was found to be very promising as a potential candidate for crush energy absorber devise. To evaluate the true crush response, a drop hammer tower facility was designed and fabricated in this study. Through this study, dynamic crush response was investigated and as suspected, indeed the “wrap” specimen displayed satisfactory crashworthiness results. Specimens made from carbon fibers displayed good specific energy absorption as high as 34.7 kJ/kg, much higher in relation to conventional metals. In depth analysis on the macroscopic failure modes was done and its relation to the energy absorption capabilities of the specimens was studied. In general, four types of failure modes were observed. Several parameters were studied to further improve the crashworthiness of the “wrap” design. These parameters basically included the dimension, material configuration and the cross sectional topology. Based on these findings, the study had contributed significantly in the area of crashworthiness by producing a potential candidate for a crush element that could be used in automotive industries and also extended to other vehicles such as buses, trains and ships.